5.1.25 Problems 2401 to 2500

Table 5.49: First order ode

#

ODE

Mathematica

Maple

5316

\[ {}\left (x -2 \sqrt {x y}\right ) y^{\prime } = y \]

5317

\[ {}\left (y+\sqrt {1+y^{2}}\right ) \left (x^{2}+1\right )^{{3}/{2}} y^{\prime } = 1+y^{2} \]

5318

\[ {}\left (y+\sqrt {1+y^{2}}\right ) \left (x^{2}+1\right )^{{3}/{2}} y^{\prime } = 1+y^{2} \]

5319

\[ {}\left (x -\sqrt {x^{2}+y^{2}}\right ) y^{\prime } = y \]

5320

\[ {}x \left (1-\sqrt {x^{2}-y^{2}}\right ) y^{\prime } = y \]

5321

\[ {}x \left (\sqrt {x^{2}+y^{2}}+x \right ) y^{\prime }+y \sqrt {x^{2}+y^{2}} = 0 \]

5322

\[ {}x y \left (x +\sqrt {x^{2}-y^{2}}\right ) y^{\prime } = x y^{2}-\left (x^{2}-y^{2}\right )^{{3}/{2}} \]

5323

\[ {}\left (x \sqrt {1+x^{2}+y^{2}}-y \left (x^{2}+y^{2}\right )\right ) y^{\prime } = x \left (x^{2}+y^{2}\right )+y \sqrt {1+x^{2}+y^{2}} \]

5324

\[ {}y^{\prime } \cos \left (y\right ) \left (\cos \left (y\right )-\sin \left (A \right ) \sin \left (x \right )\right )+\cos \left (x \right ) \left (\cos \left (x \right )-\sin \left (A \right ) \sin \left (y\right )\right ) = 0 \]

5325

\[ {}\left (a \cos \left (b x +a y\right )-b \sin \left (a x +b y\right )\right ) y^{\prime }+b \cos \left (b x +a y\right )-a \sin \left (a x +b y\right ) = 0 \]

5326

\[ {}\left (x +\cos \left (x \right ) \sec \left (y\right )\right ) y^{\prime }+\tan \left (y\right )-y \sin \left (x \right ) \sec \left (y\right ) = 0 \]

5327

\[ {}\left (1+\left (x +y\right ) \tan \left (y\right )\right ) y^{\prime }+1 = 0 \]

5328

\[ {}x \left (x -y \tan \left (\frac {y}{x}\right )\right ) y^{\prime }+\left (x +y \tan \left (\frac {y}{x}\right )\right ) y = 0 \]

5329

\[ {}\left ({\mathrm e}^{x}+x \,{\mathrm e}^{y}\right ) y^{\prime }+y \,{\mathrm e}^{x}+{\mathrm e}^{y} = 0 \]

5330

\[ {}\left (1-2 x -\ln \left (y\right )\right ) y^{\prime }+2 y = 0 \]

5331

\[ {}\left (\sinh \left (x \right )+x \cosh \left (y\right )\right ) y^{\prime }+y \cosh \left (x \right )+\sinh \left (y\right ) = 0 \]

5332

\[ {}y^{\prime } \left (1+\sinh \left (x \right )\right ) \sinh \left (y\right )+\cosh \left (x \right ) \left (\cosh \left (y\right )-1\right ) = 0 \]

5333

\[ {}{y^{\prime }}^{2} = a \,x^{n} \]

5334

\[ {}{y^{\prime }}^{2} = y \]

5335

\[ {}{y^{\prime }}^{2} = x -y \]

5336

\[ {}{y^{\prime }}^{2} = x^{2}+y \]

5337

\[ {}{y^{\prime }}^{2}+x^{2} = 4 y \]

5338

\[ {}{y^{\prime }}^{2}+3 x^{2} = 8 y \]

5339

\[ {}{y^{\prime }}^{2}+a \,x^{2}+b y = 0 \]

5340

\[ {}{y^{\prime }}^{2} = 1+y^{2} \]

5341

\[ {}{y^{\prime }}^{2} = 1-y^{2} \]

5342

\[ {}{y^{\prime }}^{2} = a^{2}-y^{2} \]

5343

\[ {}{y^{\prime }}^{2} = a^{2} y^{2} \]

5344

\[ {}{y^{\prime }}^{2} = a +b y^{2} \]

5345

\[ {}{y^{\prime }}^{2} = x^{2} y^{2} \]

5346

\[ {}{y^{\prime }}^{2} = \left (y-1\right ) y^{2} \]

5347

\[ {}{y^{\prime }}^{2} = \left (y-a \right ) \left (y-b \right ) \left (y-c \right ) \]

5348

\[ {}{y^{\prime }}^{2} = a^{2} y^{n} \]

5349

\[ {}{y^{\prime }}^{2} = a^{2} \left (1-\ln \left (y\right )^{2}\right ) y^{2} \]

5350

\[ {}{y^{\prime }}^{2}+f \left (x \right ) \left (y-a \right ) \left (y-b \right ) = 0 \]

5351

\[ {}{y^{\prime }}^{2}+f \left (x \right ) \left (y-a \right )^{2} \left (y-b \right ) = 0 \]

5352

\[ {}{y^{\prime }}^{2}+f \left (x \right ) \left (y-a \right ) \left (y-b \right ) \left (y-c \right ) = 0 \]

5353

\[ {}{y^{\prime }}^{2}+f \left (x \right ) \left (y-a \right )^{2} \left (y-b \right ) \left (y-c \right ) = 0 \]

5354

\[ {}{y^{\prime }}^{2} = f \left (x \right )^{2} \left (y-a \right ) \left (y-b \right ) \left (y-c \right )^{2} \]

5355

\[ {}{y^{\prime }}^{2} = f \left (x \right )^{2} \left (y-u \left (x \right )\right )^{2} \left (y-a \right ) \left (y-b \right ) \]

5356

\[ {}{y^{\prime }}^{2}+2 y^{\prime }+x = 0 \]

5357

\[ {}{y^{\prime }}^{2}-2 y^{\prime }+a \left (x -y\right ) = 0 \]

5358

\[ {}{y^{\prime }}^{2}-2 y^{\prime }-y^{2} = 0 \]

5359

\[ {}{y^{\prime }}^{2}-5 y^{\prime }+6 = 0 \]

5360

\[ {}{y^{\prime }}^{2}-7 y^{\prime }+12 = 0 \]

5361

\[ {}{y^{\prime }}^{2}+a y^{\prime }+b = 0 \]

5362

\[ {}{y^{\prime }}^{2}+a y^{\prime }+b x = 0 \]

5363

\[ {}{y^{\prime }}^{2}+a y^{\prime }+b y = 0 \]

5364

\[ {}{y^{\prime }}^{2}+x y^{\prime }+1 = 0 \]

5365

\[ {}{y^{\prime }}^{2}+x y^{\prime }-y = 0 \]

5366

\[ {}{y^{\prime }}^{2}-x y^{\prime }+y = 0 \]

5367

\[ {}{y^{\prime }}^{2}-x y^{\prime }-y = 0 \]

5368

\[ {}{y^{\prime }}^{2}+x y^{\prime }+x -y = 0 \]

5369

\[ {}{y^{\prime }}^{2}+\left (1-x \right ) y^{\prime }+y = 0 \]

5370

\[ {}{y^{\prime }}^{2}-\left (1+x \right ) y^{\prime }+y = 0 \]

5371

\[ {}{y^{\prime }}^{2}-\left (2-x \right ) y^{\prime }+1-y = 0 \]

5372

\[ {}{y^{\prime }}^{2}+\left (x +a \right ) y^{\prime }-y = 0 \]

5373

\[ {}{y^{\prime }}^{2}-2 x y^{\prime }+1 = 0 \]

5374

\[ {}{y^{\prime }}^{2}+2 x y^{\prime }-3 x^{2} = 0 \]

5375

\[ {}{y^{\prime }}^{2}+2 x y^{\prime }-y = 0 \]

5376

\[ {}{y^{\prime }}^{2}+2 x y^{\prime }-y = 0 \]

5377

\[ {}{y^{\prime }}^{2}-2 x y^{\prime }+2 y = 0 \]

5378

\[ {}{y^{\prime }}^{2}-\left (2 x +1\right ) y^{\prime }-x \left (1-x \right ) = 0 \]

5379

\[ {}{y^{\prime }}^{2}+2 \left (1-x \right ) y^{\prime }-2 x +2 y = 0 \]

5380

\[ {}{y^{\prime }}^{2}+3 x y^{\prime }-y = 0 \]

5381

\[ {}{y^{\prime }}^{2}-4 \left (1+x \right ) y^{\prime }+4 y = 0 \]

5382

\[ {}{y^{\prime }}^{2}+a x y^{\prime } = b c \,x^{2} \]

5383

\[ {}{y^{\prime }}^{2}-a x y^{\prime }+a y = 0 \]

5384

\[ {}{y^{\prime }}^{2}+a x y^{\prime }+b \,x^{2}+c y = 0 \]

5385

\[ {}{y^{\prime }}^{2}+\left (b x +a \right ) y^{\prime }+c = b y \]

5386

\[ {}{y^{\prime }}^{2}-2 x^{2} y^{\prime }+2 x y^{\prime } = 0 \]

5387

\[ {}{y^{\prime }}^{2}+a \,x^{3} y^{\prime }-2 a \,x^{2} y = 0 \]

5388

\[ {}{y^{\prime }}^{2}-2 a \,x^{3} y^{\prime }+4 a \,x^{2} y = 0 \]

5389

\[ {}{y^{\prime }}^{2}+4 x^{5} y^{\prime }-12 x^{4} y = 0 \]

5390

\[ {}{y^{\prime }}^{2}-2 y^{\prime } \cosh \left (x \right )+1 = 0 \]

5391

\[ {}{y^{\prime }}^{2}+y y^{\prime } = x \left (x +y\right ) \]

5392

\[ {}{y^{\prime }}^{2}-y y^{\prime }+{\mathrm e}^{x} = 0 \]

5393

\[ {}{y^{\prime }}^{2}+\left (x +y\right ) y^{\prime }+x y = 0 \]

5394

\[ {}{y^{\prime }}^{2}-2 y y^{\prime }-2 x = 0 \]

5395

\[ {}{y^{\prime }}^{2}+\left (1+2 y\right ) y^{\prime }+y \left (y-1\right ) = 0 \]

5396

\[ {}{y^{\prime }}^{2}-2 \left (x -y\right ) y^{\prime }-4 x y = 0 \]

5397

\[ {}{y^{\prime }}^{2}-\left (1+4 y\right ) y^{\prime }+\left (1+4 y\right ) y = 0 \]

5398

\[ {}{y^{\prime }}^{2}-2 \left (1-3 y\right ) y^{\prime }-\left (4-9 y\right ) y = 0 \]

5399

\[ {}{y^{\prime }}^{2}+\left (a +6 y\right ) y^{\prime }+y \left (3 a +b +9 y\right ) = 0 \]

5400

\[ {}{y^{\prime }}^{2}+a y y^{\prime }-a x = 0 \]

5401

\[ {}{y^{\prime }}^{2}-a y y^{\prime }-a x = 0 \]

5402

\[ {}{y^{\prime }}^{2}+\left (a x +b y\right ) y^{\prime }+a b x y = 0 \]

5403

\[ {}{y^{\prime }}^{2}-x y y^{\prime }+y^{2} \ln \left (a y\right ) = 0 \]

5404

\[ {}{y^{\prime }}^{2}-\left (2 x y+1\right ) y^{\prime }+2 x y = 0 \]

5405

\[ {}{y^{\prime }}^{2}-\left (4+y^{2}\right ) y^{\prime }+4+y^{2} = 0 \]

5406

\[ {}{y^{\prime }}^{2}-\left (x -y\right ) y y^{\prime }-x y^{3} = 0 \]

5407

\[ {}{y^{\prime }}^{2}+y^{2} y^{\prime } x +y^{3} = 0 \]

5408

\[ {}{y^{\prime }}^{2}-2 x^{3} y^{2} y^{\prime }-4 x^{2} y^{3} = 0 \]

5409

\[ {}{y^{\prime }}^{2}-x y \left (x^{2}+y^{2}\right ) y^{\prime }+y^{4} x^{4} = 0 \]

5410

\[ {}{y^{\prime }}^{2}+2 x y^{3} y^{\prime }+y^{4} = 0 \]

5411

\[ {}{y^{\prime }}^{2}+2 y y^{\prime } \cot \left (x \right )-y^{2} = 0 \]

5412

\[ {}{y^{\prime }}^{2}-3 x y^{{2}/{3}} y^{\prime }+9 y^{{5}/{3}} = 0 \]

5413

\[ {}{y^{\prime }}^{2} = {\mathrm e}^{4 x -2 y} \left (y^{\prime }-1\right ) \]

5414

\[ {}2 {y^{\prime }}^{2}+x y^{\prime }-2 y = 0 \]

5415

\[ {}2 {y^{\prime }}^{2}-\left (1-x \right ) y^{\prime }-y = 0 \]